Impact of Hepatic Encephalopathy on Clinical Characteristics and Adverse Outcomes in Prospective and Multicenter Cohorts of Patients With Acute-on-Chronic Liver Diseases - Long, Liyuan; Li, Hai; Deng, Guohong; Wang, Xianbo; Lu, Sihong; Li, Beiling; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Ren, Haotang; et al. (Frontiers in Medicine, 2021)
Importance: Hepatic encephalopathy is a severe complication, and its contribution to clinical adverse outcomes in patients with acute-on-chronic liver diseases from the East is unclear. Objective: We aimed to investigate the impact of hepatic encephalopathy on clinical characteristics and adverse outcomes in prospective and multicenter cohorts of patients with acute-on-chronic liver diseases. Design: We conducted a cohort study of two multicenter prospective cohorts. Setting: China. Participants: Acute-on-chronic liver disease patients with various etiologies. Exposure: The diagnosis and severity of hepatic encephalopathy were assessed using the West Haven scale. Main Outcome Measure: The correlation between clinical adverse outcomes and varying hepatic encephalopathy grades was analyzed in the target patients. Results: A total of 3,949 patients were included, and 340 of them had hepatic encephalopathy. The incidence of hepatic encephalopathy was higher in patients with alcohol consumption (9.90%) than in those with hepatitis B virus infection (6.17%). The incidence of 28- and 90-day adverse outcomes increased progressively from hepatic encephalopathy grades 1–4. Logistic regression analysis revealed that hepatic encephalopathy grades 3 and 4 were independent risk factors for the 28- and 90-day adverse outcome in the fully adjusted model IV. Stratified analyses showed similar results in the different subgroups. Compared to grades 1–2 and patients without hepatic encephalopathy, those with grade 3 hepatic encephalopathy had a significant increase in clinical adverse outcomes, independent of other organ failures. Conclusions and Relevance: Hepatic encephalopathy grades 3–4 were independent risk factors for 28- and 90-day adverse outcomes. Hepatic encephalopathy grade 3 could be used as an indicator of brain failure in patients with acute-on-chronic liver disease.